Inclusion complexation of catechin by β-cyclodextrins: Characterization and storage stability. (December 2017) - Ho, Siyin; Thoo, Yin Yin; Young, David James; Siow, Lee Fong
Abstract: The potential applications of catechin in food products are limited by its astringent taste, sparing solubility in water and sensitivity to oxygen, light and pH. A finishing formulation that is capable of protecting catechin is needed to deliver this antioxidant to its physiological targets with minimal loss of bioactivity. The aims of this study were to optimize the yield, microencapsulation efficiency and antioxidant properties of the inclusion complex (IC) and to determine the physicochemical properties and stability of β-CD-, HPβ-CD and Mβ-CD-complexed-catechin for potential functional food and health supplement applications. An inclusion complex prepared from 0.006 mol/L catechin and β-cyclodextrin (β-CD) with a 1:1 core to wall ratio showed the highest yield, encapsulation efficiency and antioxidant activity. Catechin complexed with β-CD more efficiently than with hydroxypropyl- β-cyclodextrin (HPβ-CD) or methyl- β-cyclodextrin (Mβ-CD). Encapsulation with β-CD was observed to double the water solubility of catechin. Particles of complexes ranging from 5 to 100 μm with spherical morphology were produced. 1 H NMR spectroscopy and DSC confirmed the host – guest complexation of catechin in the β-CD cavity. The current study shows that encapsulation of catechin with β-CD provides protection against temperature, light and oxygen. These inclusion complexes have potential applications as functional foods and health supplements. Highlights: Catechin is efficiently encapsulated with β-cyclodextrin. Catechin encapsulation with β-cyclodextrin doubles its water solubility. Encapsulation protects catechin against temperature, light and oxygen. Cyclodextrin inclusion complexes have potential applications in functional foods.